Study on the strength composition mechanism and interface microscopic characteristics of cold recycling asphalt mixture - Dong, Zhao; Xu, Guangji; Xu, Shudong; Ma, Shijie; Ma, Tao; Luan, Yingcheng; Liu, Jiuwei (Frontiers in Materials, 2024)
Compared to other pavement material recycling technologies, cold recycling asphalt mixture has significant economic and environmental benefits. The cold recycling mixture contains recycling asphalt pavement (RAP), new aggregate particle (NAP), asphalt emulsion, cement and fillers. The internal material composition is complex and the interface form is changeable, which has a significant impact on the mechanical properties. Therefore, this paper aims to study the influence of material composition and related content on the strength performance of cold recycling mixture from two aspects of macroscopic mechanical test and microscopic characteristics analysis. In this paper, the strength evolution law of cold recycling mixture under the change of cement, emulsified asphalt and RAP content is carried out. The test result shows that low cement content has little effect on the strength of cold recycling mixture, which is not the main factor affecting its strength composition, and the asphalt mainly plays the role of binder. Compared with the NAP, the aged asphalt mortar and emulsified asphalt mortar have better interfacial bonding effect. The surface of the NAP needs more asphalt to form structural asphalt. From the microscopic characteristics of the interfacial transition zone, the cement hydration products and asphalt mortar are intertwined to form a network structure, and the pore structure is filled with asphalt. Compared with the interface between aggregate and asphalt, cement hydration product has a poor adhesion effect with aggregate, and there are some micro-cracks in the interface transition zone, which is mainly used as an interface modifier interface improver to enhance the interface bonding effect.